1999
DOI: 10.1021/jf990414f
|View full text |Cite
|
Sign up to set email alerts
|

Current Knowledge of Soft Cheeses Flavor and Related Compounds

Abstract: Cheese aroma is the result of the perception of a large number of molecules belonging to different chemical classes. The volatile compounds involved in the soft cheese flavor have received a great deal of attention. However, there has been less work concerning the volatile compounds in the soft smear-ripened cheeses than in the mold-ripened cheeses. This paper reviews the components that contribute to the characteristic flavor in the soft cheeses such as surface-ripened, Camembert-type, and Blue cheeses. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
151
0
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(166 citation statements)
references
References 55 publications
11
151
0
4
Order By: Relevance
“…These findings agree with other authors [32]. Butanoic acid, associated by sniffers with rancid cheese, has also been reported in several unripened and ripened cheeses, and is a common constituent of cheese flavour [30].…”
Section: Characterisation Of Volatile Compoundssupporting
confidence: 93%
See 2 more Smart Citations
“…These findings agree with other authors [32]. Butanoic acid, associated by sniffers with rancid cheese, has also been reported in several unripened and ripened cheeses, and is a common constituent of cheese flavour [30].…”
Section: Characterisation Of Volatile Compoundssupporting
confidence: 93%
“…Although present at low concentrations, most of these compounds accounted for high scores in the GC-O analysis. Similar results were reported by Sablé and Cottenceau [30] in an analysis of the odour thresholds and flavour notes of these compounds in different matrices. Carunchia-Whetstine et al [9], in a study of fresh chevre-style goat cheese, found several γ-lactones related to sweet aroma and milk fat flavour.…”
Section: Characterisation Of Volatile Compoundssupporting
confidence: 90%
See 1 more Smart Citation
“…It is known that free FA, odd-carbon chain methyl ketones, and secondary alcohols are the major contributors to the characteristic flavour of blue cheese, so the flavour development during the cheese ripening is dependent on milk triacylglycerols hydrolysis by Penicillium roqueforti lipases and subsequent oxidation of FA to methyl ketones. However, a large number of other volatile compounds have been identified in blue cheeses (SABLÉ & COTTENCEAU 1999;UR REHMAN et al 2000;QIAN et al 2002).…”
Section: Identification Of Aroma Compounds In Niva Cheesementioning
confidence: 99%
“…Concerning dodecanoic acid responsible for fatty flavor, its mean concentration (11.4 µg  g -1 ) in yoghurts with low and high overall acceptability score was higher and lower than threshold in water (2.2 µg  g -1 ) and oil (50 µg  g -1 ), respectively (Molimard and Spinnler 1995;Sable and Cottenceau 1999). This result confirmed that if dodecanoic acid was much higher in yoghurts than threshold in oil, it might be negatively correlated to overall acceptability since the correlation coefficient between fat content and overall acceptability score was negative.…”
Section: Results and Discusionmentioning
confidence: 99%